ANALYSIS OF DETERMINANTS IN HALAL INDUSTRY DEVELOPMENT OF ISLAMIC FASHION INDONESIA - Vitadiar, Fachrounissa Zein (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: As Indonesia is inhabited by a lot of Muslim population, this demographic characteristic benefits the expansion of the halal industry internationally. The reputation of halal products relies on the rising production quality. This study aims to better understand how fashion preferences, halal certification, and the quality of business actors influence the potential of the Indonesian Islamic fashion industry to become an international halal industry. Methods: This study was carried out using quantitative analyses including multiple linear regression, validity, and reliability analyses. Results: The quality of business actors, halal certification, and fashion taste all had a positive and significant effect on expanding the potential of the Islamic halal fashion trade. Conclusion and suggestion: The Indonesian Ulema Council and the government should coordinate in ascending the halal certification. In addition, business actors are required to seek information related to halal certificates and acquire them before running their business. Given the importance of halal certification, the public is encouraged to purchase halal fashion items as this lifestyle expresses their identity.